Implementing Internet Of Things (IOT) Technology For Real-Time Detection And Monitoring Of LPG Gas Leaks - Effendi, M Makmun; Zy, Ahmad Turmudi; Sanudin, Sanudin (SEAN Institute, 2024)
The Currently, LPG (Liquefied Petroleum Gas) is a vital resource for many households in Indonesia, as highlighted by the government's initiative to convert from kerosene to gas as a cooking fuel. The widespread adoption of LPG is attributed to its affordability and efficiency. However, the flammable nature of LPG poses significant risks, particularly in the event of leaks, which can lead to explosions and fires. This research aims to develop a system that monitors and detects gas leaks in real-time to prevent such hazardous incidents. The proposed system utilizes Internet of Things (IoT) technology, incorporating MQ-6 gas sensors and Raspberry Pi to detect LPG leaks. The MQ-6 sensors are capable of identifying the presence of gas, while the Raspberry Pi processes the data and sends notifications in the event of a leak. The methodology includes literature reviews, user interviews, and data analysis to design an effective monitoring system. The results indicate that the system can accurately detect gas leaks and provide real-time alerts via SMS or a mobile application. In conclusion, this study demonstrates that an IoT-based monitoring and detection system for LPG leaks can significantly enhance safety by enabling prompt responses to gas leaks. This system not only benefits users by facilitating quicker leak management but also contributes to broader safety measures in residential and commercial environments.